A strategic analysis of moving the state capital impact on Indonesia's economic - Lisbet Situmorang; Badrudin Nasir; Hartutiningsih; Derin Manis Saputri (Jurnal Studi Komunikasi, 2023)
The relocation of a state's capital has garnered significant attention in expert discussions, with various perspectives being analysed. This study specifically examines the economic implications of moving the State Capital (IKN) from the standpoint of people's economic development. The primary research question explores how this relocation will affect the population's economic development. Utilising a descriptive qualitative research approach, this study gathered data through documentation, drawing from existing literature on capital relocation. Data analysis involved three stages: data reduction, presentation, and conclusion. A key finding of this research indicates that relocating the national capital positively impacts economic development, particularly benefiting micro, medium, and small enterprises. The new capital city is expected to foster the emergence of numerous small and medium enterprises driven by the increasing demand for infrastructure. Properly situating the national capital is anticipated to stimulate economic growth and promote more equitable development, unlike a Java-centric approach that could lead to imbalanced economic growth.